2020
DOI: 10.1007/s10856-020-06434-1
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3ε protein-loaded 3D hydrogels favor osteogenesis

Abstract: 3D printing has emerged as vanguard technique of biofabrication to assemble cells, biomaterials and biomolecules in a spatially controlled manner to reproduce native tissues. In this work, gelatin methacrylate (GelMA)/alginate hydrogel scaffolds were obtained by 3D printing and 14-3-3ε protein was encapsulated in the hydrogel to induce osteogenic differentiation of human adipose-derived mesenchymal stem cells (hASC). GelMA/alginate-based grid-like structures were printed and remained stable upon photo-crosslin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…[ 18 ] hAD‐MSCs were cultured and incubated with ODM as previously described. [ 14,19 ] Briefly, for all experiments, hAD‐MSCs were seeded on tissue culture treated wells, coverslips, or previously sterilized (UV light 20 min) scaffolds at 40,000 cells/cm 2 , and grown in standard culture conditions (DMEM, 10% FBS, 100 U/mL penicillin/streptomycin, 37°C, 5% CO 2 ) for 7 days. Isolations from three independent donors in young passages (2 to 4) were used.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 18 ] hAD‐MSCs were cultured and incubated with ODM as previously described. [ 14,19 ] Briefly, for all experiments, hAD‐MSCs were seeded on tissue culture treated wells, coverslips, or previously sterilized (UV light 20 min) scaffolds at 40,000 cells/cm 2 , and grown in standard culture conditions (DMEM, 10% FBS, 100 U/mL penicillin/streptomycin, 37°C, 5% CO 2 ) for 7 days. Isolations from three independent donors in young passages (2 to 4) were used.…”
Section: Methodsmentioning
confidence: 99%
“…The material was processed to obtain the hAD-MSCs from the stromal vascular fraction, and cell characterization was conducted by flow cytometry analysis (CD105, CD90, CD73 positive markers, and CD45, CD34, CD11b, CD19, HLA-DR negative markers) and by differentiation to adipogenic and osteogenic lineages as in Gojanovich et al [18] hAD-MSCs were cultured and incubated with ODM as previously described. [14,19] Briefly, for all experiments, hAD-MSCs were seeded on tissue culture treated wells, coverslips, or previously sterilized (UV light 20 min) scaffolds at 40,000 cells/cm 2 , and grown in standard culture conditions (DMEM, 10% FBS, 100 U/mL penicillin/streptomycin, 37 • C, 5% CO 2 ) for 7 days. Isolations from three independent donors in young passages (2 to 4) were used.…”
Section: Had-mscs Preparation Characterization Cultivation and Osteog...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have found that GelMA hydrogels can enhance the ability of MSCs to transform into osteoblasts and effectively control TGF release. , Aldanan et al . found that GelMA/AlgH hydrogel loaded with 14-3-3ε protein enhanced the ability to induce osteoblast differentiation of human MSCs.…”
Section: Therapeutic Mechanism Based On the Gelma Hydrogel Systemmentioning
confidence: 99%